ANALISA PENGARUH GAYA KEPEMIMPINAN DAN KOMUNIKASI TERHADAP KINERJA KARYAWAN PADA PT ANTAR NUSA JAKARTA - Parmin, Yohanes (Sekolah Tinggi Ilmu Ekonomi Bhakti Pembangunan, 2024)
The purpose of this research is to determine the influence of leadership style and communication on employee performance at PT Proteksi Antar Nusa Jakarta. The data collection method was carried out through distributing questionnaires to all 54 employees of PT Proteksi Antar Nusa Jakarta. Data analysis in this research used SPSS VERSION 24. The sampling technique used was a survey and distribution of questionnaires to employees and testing of the data used in the research used the Simple Random Sampling method. Data analysis in this research used Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, Determination Coefficient Test, T Test, and F Test. From the research results of the Determination coefficient test, adjusted R2 obtained a value of 0.820 or 82%. This shows that 82% of employee performance is influenced by leadership style and communication variables, while the remaining 18% is influenced by other variables such as competence, discipline, etc. In the t test, the calculated t value for the leadership and communication style variables respectively is 2.496 and 2.210, which is greater than t table 2.009 with a probability level of 0.016, 0.032, and 0.024 respectively which is smaller than the alpha probability of 0.05, so that partially the style variable Leadership and communication have a significant effect on the performance of PT Proteksi Antar Nusa Jakarta employees. The F test produces an Fcount value of 81.474 which is greater than Ftable 2.79. Then, with a significance level of 0.000, it is smaller than the alpha probability level of 0.05 so that simultaneously the leadership style and communication variables have a significant effect on employee performance.